(untitled) (Journal of Scientific Research, 2017)
The study was conducted in Mongla tidal river (Rampal) of Bagerhat district from November 2014 to October 2015 to assess the abundance of black tiger shrimp (Penaeus monodon) post larvae (PL) and to quantify the damage of different aquatic fauna during collection of P. monodon PL. Insignificant variation in water temperature, pH, salinity and hardness were found but salinity and hardness showed great fluctuation during the study period. On average 6.3 million of P. monodon PL were collected annually from the studied area and around 0.16 million man days/year were estimated to be involved in shrimp PL collection activities. It was found that about 412 other shrimp larvae, 391 fin fishes and 1696 other macrozooplankton were killed during the period of collection for only one PL of P. monodon. It was also calculated from the present study that about 29,874 million of other shrimp species, fin fishes and macrozooplankton were destroyed annually by the shrimp seed harvesting process in Mongla river. The study implies that present seed collection practice caused severe damage of other valuable aquatic fauna, which directly affect the biodiversity of tidal waters, natural productivity, improvement of mother stock and environment friendly of coastal and marine water.